Biases in Attention for Social Stimuli in Children are Associated with Patterns of Infant Attachment: A Brief Report. Issue 1 (6th March 2016) - Meinz, Paul; Morton, J. Bruce; Pederson, David R.; Moran, Greg
Abstract: The way an individual attends to social information has implications for his/her ability to regulate behavior in social settings. The results of the present investigation suggest that early experiences in parent–child relationships contribute to later differences in the deployment of attention to social information. The quality of the mother–child relationship was assessed at one‐year‐of‐age. At seven to eight years of age, a dot‐probe paradigm assessed immediate and delayed attention to pictures of faces vs. pictures of neutral objects. Children who were more avoidant with their mother in infancy attended to neutral objects over social stimuli at delayed but not immediate time frames. This finding suggests that individual differences in attention to social stimuli in childhood are associated with the quality of the prior attachment relationship with a primary caregiver.